Young Onset Colorectal Cancer - Pakalnickaitė, Emilija; Dulskas, Audrius (Lietuvos chirurgija, 2025)
Early onset colorectal cancer - colorectal cacner, appearing in a patient population below 50 years of age. Disease is more aggressive, and diagnosis is more likely in an advanced stage. The increase in the incidence of this form of disease globally requires more mature prevention and treatment options.
Keywords: colorectal cancer in young people; epidemiology; pathogenesis; treatment methods; genetic factors